Pemanfaatan Multimedia Interaktif dalam Meningkatkan Minat Belajar Siswa Kelas VIII pada Pembelajaran PKn di MTs Sabilit Taqwa - Anwar, Khairul; Jusrianto, Jusrianto; Nur, Haspidawati; Parubang, Daniel (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2024)
This article discusses the Use of Interactive Multimedia in Increasing Class VIII Students' Interest in Learning in Civics Learning at MTs Sabilit Taqwa. This research focuses on the Civics learning process using Interactive Multimedia learning media. This research uses a quantitative research approach. data collection instruments through observation, questionnaires and documentation. Data analysis uses descriptive. Utilization of Interactive Multimedia in Increasing Class VIII Students' Interest in Learning in Civics Learning at MTs Sabilit Taqwa. Based on the results of the research that has been carried out, it can be concluded that Civics learning using Interactive Multimedia Learning Media can increase the learning interest of class VIII students at MTs Sabilit Taqwa with a population of 25 students. Based on the results of this research, the researcher concluded that the use of interactive multimedia is very effective in increasing the learning interest of class VIII/PKn students at MTs Sabilit Taqwa. This is supported by the average student score. The students' average score on the initial test was 71.84 lower than on the final test, 89.12. In addition, Î± is higher than p-value (0.05 0.00). This shows that the null hypothesis is rejected and H1 is accepted. This shows that the use of interactive multimedia is very effective in increasing the learning interest of class VIII/Civics students at MTs Sabilit Taqwa.